2021
DOI: 10.1186/s12864-021-08118-8
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the role of male reproductive tract and haemolymph in cantharidin-exuding Lydus trimaculatus and Mylabris variabilis (Coleoptera: Meloidae): a comparative transcriptomics approach

Abstract: Background Meloidae (blister beetles) are known to synthetize cantharidin (CA), a toxic and defensive terpene mainly stored in male accessory glands (MAG) and emitted outward through reflex-bleeding. Recent progresses in understanding CA biosynthesis and production organ(s) in Meloidae have been made, but the way in which self-protection is achieved from the hazardous accumulation and release of CA in blister beetles has been experimentally neglected. To provide hints on this pending question, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 135 publications
0
13
0
Order By: Relevance
“…In a previous paper, NGS-based transcriptome analyses of adult samples of L. trimaculatus and M. variabilis performed by Fratini et al [ 33 ] revealed several proteins involved in the regulation of coagulation from the whole body, accessory gland, and haemolymph. The gene and protein sequences codifying for Bovine Pancreatic Trypsin Inhibitor (BPTI, mRNA: NM_001001554.3; Protein: NP_001001554.2) and Kunitz-Type protease inhibitors of A. glabripennis (mRNA: XM_018715645.1; Protein: P_018571161.1) were blasted against the transcriptome of L. trimaculatus and M. variabilis to identify homologous sequences in these species.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In a previous paper, NGS-based transcriptome analyses of adult samples of L. trimaculatus and M. variabilis performed by Fratini et al [ 33 ] revealed several proteins involved in the regulation of coagulation from the whole body, accessory gland, and haemolymph. The gene and protein sequences codifying for Bovine Pancreatic Trypsin Inhibitor (BPTI, mRNA: NM_001001554.3; Protein: NP_001001554.2) and Kunitz-Type protease inhibitors of A. glabripennis (mRNA: XM_018715645.1; Protein: P_018571161.1) were blasted against the transcriptome of L. trimaculatus and M. variabilis to identify homologous sequences in these species.…”
Section: Resultsmentioning
confidence: 99%
“…The transcriptomic analysis conducted on two species of blister beetle [ 33 ] allowed broadening the knowledge about the transcripts expressed in L. trimaculatus and M. variabilis , also opening the possibility to isolate new proteins with potential biotechnological and biomedical functions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations